Consumer Satisfaction of Sorabel Applications Using the Delone and Mclean Method - Dari, Wulan; Prahartiwi, Lusa Indah (LPPM Universitas Islam 45 Bekasi, 2020)
The rapid development of information technology influences on all fields of the economy. One form of the development of information technology is about how consumers shop through online stores. Researchers need to do this research because nowadays there are many online stores that have developed in Indonesia. Researchers want to know how much influence the quality of information and service quality on customer satisfaction and make a positive contribution and make continuous purchases at the online store. This study uses the Delone and Mclean methods and with AMOS software. The purpose of this study is to analyze a number of hypotheses, which are: H1: System Quality has a positive effect on Use; H2: Use has a positive impact on net benefits; H3: System Quality has a positive impact on User Satisfaction; H4: User Satisfaction has a positive effect on Use; H5: Information Quality has a positive effect on Use; H6: Information Quality has a positive effect on User Satisfaction; H7: User Satisfaction has a positive effect on Net benefits; H8: System Quality has a positive effect on Information Quality; H9: Information Quality has a positive effect on System Quality. The test results can be seen that Quality System has a positive effect on User Satisfaction, this can be seen from the estimated value of 0.529, User Satisfaction has a positive effect on the Net benefits that can be seen from the estimated value of 1,146, and User Satisfaction has a positive effect on Use with an estimated value of 1,352. From the test results with the final research model that supports the hypothesis (H0) said that there is a relationship between variables with the level of satisfaction of the Sorabel Application to the Sorabel Application user as a medium for online purchases